Economic impact of enhanced recovery after surgery protocol in minimally invasive cardiac surgery - Johannes Petersen; Benjamin Kloth; Johanna Konertz; Jens Kubitz; Leonie Schulte-Uentrop; Gesche Ketels; Hermann Reichenspurner; Evaldas Girdauskas (BMC, 2021)
Abstract Background ERAS (Enhanced Recovery After Surgery) is a multidisciplinary and integrative approach with the goal of optimizing the postoperative recovery. We aimed to analyze the economic impact of a newly established ERAS protocol in minimally invasive heart valve surgery at our institution. Methods ERAS protocol was implemented in 61 consecutive patients who were referred for elective minimally-invasive aortic or mitral valve surgery, between February 1, 2018 and March 31, 2019 (ERAS-group). Another 69 patients who underwent elective minimally-invasive heart valve surgery during the same time period were managed according to the hospital standards (Control-group). A detailed cost comparison analysis was carried out from a hospital perspective using a micro-costing approach. Results The total in-hospital stay was significantly shorter in the ERAS-group compared to the Control-group (6.1 ± 2.6 vs 7.7 ± 3.8 days; p = 0.008) resulting in significant cost savings of €1087.2 per patient (p = 0.003). Due to the intensified physiotherapy in the ERAS protocol, the costs for physiotherapy were €94.3 higher compared to the Control-group (p < 0.001). The total costs in the ERAS cohort were €11,200.0 ± 3029.6/patient compared to € 13,109.8 ± 4527.5/patient in the Control-Group resulting in cost savings of €1909.8 patient due to the implementation of the ERAS protocol (p = 0.006). Conclusion Implementation of an ERAS-protocol in minimally-invasive cardiac surgery can be carried out safely with a fast postoperative recovery of the patient. ERAS results in a financial benefit of up to €1909 per patient and therefore will play a key role in modern cardiac surgery in the near future.